Pengaruh Penerapan Sistem E-billing dan Penegakan Hukum Perpajakan Terhadap Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak Pratama Makassar - Wahyuni, Nur (STIM-LPI Makassar, 2024)
This research aims to determine and analyse : (1) the effect of the e-Billing system on taxpayer compliance at KPP Pratama Makassar, (2) the effect of tax law enforcement on taxpayer compliance at KPP Pratama Makassar, (3) the effect of the e-Billing system and enforcement. tax law simultaneously on taxpayer compliance at KPP Pratama Makassar. This research is a type of quantitative research, with the research population of 98. 953 taxpayers registered at KPP Pratama Makassar Utara. The sampling technique used simple random sampling in order to obtain a sample size of 100 taxpayers. The data collection technique used a questionnaire. The data analysis technique used in this research is descriptive analysis and multiple linear regression analysis. The results of this research indicate that : (1) the application of the e-Billing system has a positive and significant effect on taxpayer compliance at KPP Pratama Makassar Utara, (2) tax law enforcement has a positive and significant effect on taxpayer compliance at KPP Pratama Makassar Utara, (3) the implementation of the e-Billing system and the enforcement of Taxation law together have an effect on taxpayer compliance at KPP Pratama Makassar Utara.